Análise da Dysphania ambrosioides como agente protetor da perda de massa óssea - RIBEIRO, Ludmila Pantaroto Lima (2023)
Glucocorticoids have adverse effects that can trigger loss of bone mineral density. There is evidence that Dysphania ambrosioides can prevent bone loss. The aim of this study was to analyze possible effects of Dysphania ambrosioides consumption on bones of female rats submitted to induction of loss of bone mineral density by using dexamethasone for 7 weeks. Forty female Wistar rats were divided into four groups: control group (CT), dexamethasone group (Dexa), dexamethasone ambrosoides 25 mg/kg group (Ambro1) and dexamethasone ambrosoides 500 mg/kg (Ambro2) group. Qualitative and quantitative analyzes were performed on the crude hydroalcoholic extract of Dysphania ambrosioides, identifying the presence of saponins 0.618 μg/ml, flavonoids 2.174 μg/ml, tannins 63.44 μg/ml and alkaloids 0.107 μg/ml. Dexamethasone was applied twice a week, while Dysphania ambrosioides was administered daily. Weekly weight control showed weight loss in the groups that received dexamethasone, with loss attenuation in Ambro2. After the euthanasia of the animals, structural and material properties were analyzed and Raman analysis of the femurs. In the mechanical test, the CT group showed higher values of maximum force compared to the Dexa and Ambro2 groups, and was statistically similar with the three groups both for absolute strain and for structural stiffness. The Dexa group was less resistant to force application than the Ambro1 group, which was similar to the CT group. CT showed a higher value for maximum tension in relation to the Dexa and Ambro2 groups, and similar in relation to the Ambro1 group. The Ambro1 group withstood greater tension compared to the Dexa and Ambro2 groups. CT and Ambro1 showed higher elastic modulus values, the CT group showed a difference in relation to the Dexa and Ambro2 groups, and the Ambro1 group showed a difference when compared to the Dexa and Ambro2 groups. In the Raman analysis, the 430/1270 ratio showed no statistical difference between the four groups. The ratio 960/1660, the CT group showed a difference between the other groups, and the Dexa group showed a difference between the Ambro2. The 1070/1660 ratio showed a statistical difference between the CT group and the oand hus, it was possible to observe that Dysphania ambrosioides has promising effects related to increased bone strength through the induction of osteoporosis by glucocorticoids.